Activity Tests of Bioactive Material of Salung Leaf (Psychotria viridiflora Reinw. Ex. Blume) against Salmonella thypi Bacteria In Vitro And In Vivo - SALNI SALNI; HANIFA MARISA; HARMIDA HARMIDA (JURNAL ILMU KEFARMASIAN INDONESIA, 2016)
Activity test of bioactive material of Salung leaf (Psychotria viridiflora Reinw. ex. Blume) against Salmonella thypi in vitro and in vivo has been carried out. Bioactive material was obtained from the maceration and followed by fractionation of liquid-liquid fractionation. Antibacterial activity test performed in vitro to determine the value of the minimum inhibitory concentration (MIC) and in vivo to determine the ability of bioactive cure diarrhea in in rats (Rattus norvegicus) infected by Salmonella typhi. Treatment of bioactive material given is 0, 10, 50 and 100 mg kg-1 of weight. The results showed that the MIC of salung leaf’s bioactive material to Salmonella typhi was 250 μg mL-1. Bioactive ingredient at dose of 10 and 50 mg kg-1 were able to decrease the number of bacterial colonies to 4.14x106 cfu g-1 and 5.4x105 cfu g-1, less than 5.04x106 cfu g-1 as control. Bioactive material in weight of 100 mg kg-1 of weight could reduce the population of Salmonella typhi to zero after 12 days of treatment. The ability to reduce the amount of bacterial colonies of the bioactive material 100 mg kg-1 of weight is equal to the ability of positive control chloramphenicol 10 mg kg-1 of weight.